Complete remission induced by tacrolimus and low-dose prednisolone in adult minimal change nephrotic syndrome: A pilot study - Yong Chul Kim; Tae Woo Lee; Hajeong Lee; Ho Suk Koo; Kook-Hwan Oh; Kwon Wook Joo; Suhnggwon Kim; Ho Jun Chin (The Korean Society of Nephrology, 2012)
Background: Few clinical trials have examined the replacement of steroids with other immunosuppressive drugs as a primary treatment modality for minimal change disease (MCD) in adults. We studied the efficacy of tacrolimus to induce complete remission (CR) in adults with MCD. Methods: We enrolled 14 adults with MCD and nephrotic-range proteinuria. All patients were treated with oral tacrolimus 0.05 mg/kg twice daily and prednisolone 0.5 mg/kg/day. CR was defined as a urine protein to creatinine ratio of<0.2 g protein/g creatinine (g/g cr). The primary outcome was cumulative percentage of CR during 16 weeks. Results: The mean urine protein to creatinine ratio at enrollment was 10.9 g/g cr (range: 4.2-18.1 g/g cr). The trough tacrolimus level was maintained at 5.99±2.63 ng/mL. CR was achieved by 13/14 (92.8%) patients within 8 weeks. The cumulative CR rate was 7.7% (1/14), 64.2% (9/14), 71.3% (10/14), and 92.9% (13/14) at 1 week, 2 weeks, 4 weeks, and 8 weeks, respectively. The one remaining patient achieved CR at 20 weeks after treatment, who was followed up for a further 4 weeks. The mean time to achieve CR in the 14 patients was 4.64±5.11 (1-20) weeks. Three cases suffered adverse events of abdominal pain, diarrhea, or new-onset diabetes mellitus. Conclusion: Tacrolimus and low-dose prednisolone therapy induced CR rapidly (71.3% by 4 weeks and 100% by 20 weeks) and effectively in adult patients with MCD.